Morphosyntactical Errors in Students' Recount Text - Atika Nur Alami Harahap; Nurlela Nurlela; Umar Mono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The aims of the study are to identify the morphosyntactical errors which occur in students’ recount text, to describe the most and least of morphosyntactical errors in students’ recount text and to explain the reason of morphosyntactical errors occurrence in students’ recount text by XI AK at SMK Kartika 1-3 Medan. The primary data are all word, phrases and sentences in students’ recount text in the 2020 period. The method used was the qualitative method. The result of the research identified types of morphosyntactical errors; noun morphology, verb morphology, adverb morphology, adjective morphology, noun phrase, verb phrase, word order and transformation. Based the theory used to identify the error is adapted by dulay surface taxonomy, which are; addition, ommission, misorder, and misformation.  Misformation of verb morphology is the most frequent error made by the student around 45% of the total error came from this error and parameter. The second most frequently error are ommission of noun phrase with the total error sum up to 21%, misordering of noun morphology 13%, addition of verb 11%, addition of word order 8%, the last adverb and adjective morphology 1%. On the other hand, transformation parameters in all errors didn’t occur due to the monotonous of sentences used by student. Almost all the sentences are in the form of declarative sentence with a positive statement form. This research concludes that the student less of information about the use verb 2 in recount text, so they just write what they know and the student confused in used verb especially changed verb 1 into verb 2 in recount text. The reason behind this error is due to ‘Misconception’ of the student.